Photosystem I integrated into mesoporous microspheres has enhanced stability and photoactivity in biohybrid solar cells. (June 2021) - Teodor, Alexandra H.; Thal, Lucas B.; Vijayakumar, Shinduri; Chan, Madison; Little, Gabriela; Bruce, Barry D.
Abstract: Isolated proteins, especially membrane proteins, are susceptible to aggregation and activity loss after purification. For therapeutics and biosensors usage, protein stability and longevity are especially important. It has been demonstrated that photosystem I (PSI) can be successfully integrated into biohybrid electronic devices to take advantage of its strong light-driven reducing potential (−1.2V vs. the Standard Hydrogen Electrode). Most devices utilize PSI isolated in a nanosize detergent micelle, which is difficult to visualize, quantitate, and manipulate. Isolated PSI is also susceptible to aggregation and/or loss of activity, especially after freeze/thaw cycles. CaCO3 microspheres (CCMs) have been shown to be a robust method of protein encapsulation for industrial and pharmaceutical applications, increasing the stability and activity of the encapsulated protein. However, CCMs have not been utilized with any membrane protein(s) to date. Herein, we examine the encapsulation of detergent-solubilized PSI in CCMs yielding uniform, monodisperse, mesoporous microspheres. This study reports both the first encapsulation of a membrane protein and also the largest protein to date stabilized by CCMs. These microspheres retain their spectral properties and lumenal surface exposure and are active when integrated into hybrid biophotovoltaic devices. CCMs may be a robust yet simple solution for long-term storage of large membrane proteins, showing success for very large, multisubunit complexes like PSI. Graphical abstract: Membrane proteins represent >25% of most genomes. The largest membrane protein with a known structure is photosystem I (PSI), which is of interest for biotechnological applications for its photogenerated reducing potential. Most membrane proteins are isolated using detergents, rendering them prone to activity loss and degradation. We report a method for stabilization of PSI in uniform, non-aggregating mesoporous microspheres based on CaCO3 templates with retained photochemical activity and improved stability and activity when incorporated in biohybrid photovoltaic devices. Image 1